ANALISIS DAMPAK VARIASI PEMBEBANAN TERHADAP KARAKTERISTIK KELUARAN GENERATOR DI PLTMH UNIT A1 ANDUNGBIRU TIRIS PROBOLINGGO - Sinta Pratiwi; Teguh Utomo; Rini Nur Hasanah (Jurnal Mahasiswa TEUB, 2023)
From 2019 until 2020, Microhydro Power Plant (MHP) Units A1 and A2 measured a significant power decrease of more than 75% from their template capacities. Therefore, CSR PT PJ Paiton with PKSDAL Brawijaya University created a program called “Increasing The Power Capacity Of Andungbiru MHP Units A1 And A2 For The Lead Of Safe And Sustainable Electricity In 2022”. In this experiment, Unit A1 will be used as the test object, as the purpose it is to measure the success of the increasing electrical power and quality programs of Andungbiru’s MHP, especially Unit A1. The success analysis needed is in terms of increasing generator power, stability of generator output characteristics, and knowing the level of quality or efficiency of the generator after repairs and also knowing the level of stability of the generator when a fault occurs. The test is carried out in various loadings to get results that can represent the use of Andungbiru’s MHP consumers with a Dummy Load test device and a data logger with the Mod Bus Tool application with RS482 Cable Driver with load intervals of 25%-50%-75%-100%. The characteristics of the generator are considered quite good from the relationship between the variables.Keywords – MHP, Synchronous Generator, Load Variation, Electrical Impact, Desa Andungbiru, Kecamatan Tiris, Kabupaten Probolinggo